Analysis of Students' Entrepreneurial Intention Through Entrepreneurship Education and Motivation (Case Study of Students of the Qur'anic Interpretation Study Program at IAIN Bukittinggi) - M. Hasbi Nasution; Hendra Lukito; Rahmi Rahmi (Institute of Computer Science (IOCS), 2022)
This study aims to determine how the influence of entrepreneurship education and motivation on students' intentions in entrepreneurship. .This study uses a survey method with a data measurement technique using a 5 point Likert scale with a sample selection technique using the purpose sampling method Islamic high school IAIN Bukittinggi.as for the respondents of this study were students who had taken and are currently taking entrepreneurship education courses (semesters 5 & 7) with a total number of respondents as many as 84 students. .Based on the results of data collection and processing through SPSS, it is found that from the proposed hypothesis it can be concluded that entrepreneurship education and entrepreneurship motivation separately have the same positive and significant influence on entrepreneurial intentions. .then at the same time both of them also have a positive and significant influence on entrepreneurial intentions. Thus, the higher the education and entrepreneurial motivation given, the better the entrepreneurial intentions of students.